The Impact of Physical Activity on Depression Treatment: A Literature Review - Sieniawska, Daria; Sieniawska, Julia; Proszowska, Patrycja (Quality in Sport, 2024)
Introduction Engaging in physical exercise can have a significant impact on the treatment of mild-to-moderate mental health conditions, including depression. Existing antidepressant medications have limited clinical effectiveness as they fail to achieve a complete response in around 30% of depressed patients and do not induce remission in these individuals. Physical exercise can enhance the effects of antidepressant therapy in individuals with depression by boosting the health of neurons and improving the responsiveness to medication. Aim of the study The aim of the study is to investigate the role of physical activity in in the management of mental health diseases, especially depression. Materials and methods This study represents the current state of knowledge about the antidepressant effects of physical activity, particularly in the context of depressive disorders. It presents a comprehensive overview of how regular exercise can serve as an effective therapeutic strategy for managing depressive symptoms. PubMed and Google Scholar database was searched for articles written in English. The search included the keywords. Results Regular exercise significantly alleviates depressive symptoms through various mechanisms. Exercise enhances the production of endorphins, which improve mood and reduce anxiety. It also influences neurotransmitter systems, including serotonin, dopamine, and norepinephrine, which are crucial in regulating mood and emotion. Additionally, physical activity stimulates the production of brain-derived neurotrophic factor (BDNF) and transforming growth factor-beta 1 (TGF-β1), both of which support neurogenesis and synaptic plasticity, contributing to improved cognitive function and mood stabilization.